Rancang Bangun Sistem Kontrol Alat Unwider Green Hose Dengan Motor 3 Phasa - Setiawan , Wahyu; Cahyono, Muhammad Ridwan Arif (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2024)
PT. CRI is a company in the manufacturing industry that processes rubber raw materials into various products. An example is the various types of hoses produced by the Hose Production department. An unwinding tool is needed to deliver the green hose to the covering machine. In making this happen, the unwinding process is still done manually using a lorry and the operator rotates the pan by hand. As a result, the operator's work effectiveness is still low. Based on the description that has been mentioned, it is hoped that this research can present an automatic unwinding tool with a 3-phase motor as a driver and a photoelectric sensor as a trigger that can be controlled by rotating speed on the control panel so that it can facilitate work during the covering process in the hose production section.